Advocate General at the Court of Justice: any doubts? Part I - Valančius, Virgilijus (Teisė, 2020)
The article briefly overviews some features of Advocates General of the Court of Justice of the European Union as well as the influence of their opinions on the case law of the Court. The research is based on the doctrine as well as on the case law. The latter spotlights inter alia the links between the opinions of Advocates General and the judgments of the Court both when propositions of Advocates General are followed and when they are not.
Keywords: European Union law; Court of Justice; Advocate General